2006
DOI: 10.1063/1.2201445
|View full text |Cite
|
Sign up to set email alerts
|

Selective and reversible control of a chemical reaction with narrow-band infrared radiation: HXeCC radical in solid xenon

Abstract: The light-induced H + XeC 2 ↔ HXeCC reaction is studied in solid Xe, and the full optical control of this reaction is demonstrated. By narrow-band excitation in the IR spectral region, HXeCC radicals can be decomposed to a local metastable configuration and then selectively recovered by resonant excitation of the XeC 2 vibrations. The novel recovery process is explained by short-range mobility of the reagents promoted by vibrational energy redistribution near the absorbing XeC 2 molecule. This means that a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
(13 reference statements)
1
15
1
Order By: Relevance
“…40 Furthermore, it has been suggested previously that HXeI and HXeCC recover via tunneling of hydrogen after IR decomposition. 6,7 We suppose that the tunneling mechanism is very probable for the HArF formation, which contradicts with the theoretical conclusions of Bihary et al 15 Importantly for the present study, tunneling of hydrogen atoms may occur only through a short distance, which further evidences the locality of both the HF photodissociation and HArF formation in solid argon. It looks plausible that HArF is formed at low temperatures from the same H atoms as upon annealing at 20 K. This conclusion is supported by the stability of the HArF concentration upon annealing at 20 K after a long period at 8 K. On the other hand some amount of unstable HArF is probably reorganized to stable HArF at this temperature, 22 but hopefully it is not the dominating channel.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…40 Furthermore, it has been suggested previously that HXeI and HXeCC recover via tunneling of hydrogen after IR decomposition. 6,7 We suppose that the tunneling mechanism is very probable for the HArF formation, which contradicts with the theoretical conclusions of Bihary et al 15 Importantly for the present study, tunneling of hydrogen atoms may occur only through a short distance, which further evidences the locality of both the HF photodissociation and HArF formation in solid argon. It looks plausible that HArF is formed at low temperatures from the same H atoms as upon annealing at 20 K. This conclusion is supported by the stability of the HArF concentration upon annealing at 20 K after a long period at 8 K. On the other hand some amount of unstable HArF is probably reorganized to stable HArF at this temperature, 22 but hopefully it is not the dominating channel.…”
Section: Discussioncontrasting
confidence: 99%
“…24 Moreover, the recovery of HXeCC and HXeI after IR decomposition are local processes presumably involving quantum tunneling of hydrogen atoms. 6,7 The local mechanism of the HArF formation seems to be different from the cases of other HNgY molecules in Kr and Xe matrices formed mainly upon global mobility of hydrogen atoms activated by thermal annealing. 25 To investigate the question of the HArF formation scale is the main motivation of the present work.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The formation mechanism of HNgY molecules has been thoroughly discussed. It has been concluded that these molecules most probably form from the neutral H + Ng + Y fragments upon thermally activated atomic diffusion in solid noble gases [24][25][26]. An intriguing question is whether the HNgY molecules can exist as isolated molecules in the gas phase or as solidphase aggregates.…”
Section: Introductionmentioning
confidence: 97%
“…Many transient radicals have also been studied in solid noble-gas matrices [51][52][53]. Indeed, the inert matrix can be used to keep the radicals from interacting with one another, and in general the number of radicals can be built up using long deposition times.…”
Section: Introductionmentioning
confidence: 99%